The Effect of Mindfulness-Based Cognitive Therapy on Rumination Behavior among Dormitory-Dwelling Migrant Students at Universitas Teknologi Sumbawa - Miftahul Ummah; Elinda Yanti (CV Projurnal Mitra Publikasi, 2025)
Students living in university dormitories often experience academic and social adjustment demands that may increase psychological vulnerability, particularly in the form of rumination. Persistent rumination can negatively affect emotional regulation, stress management, and overall psychological well-being. Mindfulness-Based Cognitive Therapy (MBCT) has been recognized as an intervention that helps individuals develop present-moment awareness and reduce maladaptive repetitive thinking patterns. This study aims to determine the effectiveness of MBCT in reducing rumination levels among senior residents at the dormitory of Sumbawa University of Technology. The research employed a quasi-experimental design using a pretest–posttest control group model involving 18 senior residents divided into an experimental group (n = 10) and a control group (n = 8). The experimental group received MBCT intervention, while the control group received no treatment. Rumination levels were measured before and after the intervention using a standardized rumination scale. Descriptive statistical analysis indicated that the experimental group experienced a more consistent decrease in rumination scores compared to the control group. Furthermore, the Independent Samples t-Test revealed a significant difference between posttest scores of the experimental and control groups (p < 0.05), suggesting that the observed changes were associated with the intervention. These findings indicate that MBCT has significant potential as an effective psychological intervention to reduce rumination and assist students in managing psychological pressure within academically demanding environments.